2016
DOI: 10.3892/mmr.2016.5925
|View full text |Cite
|
Sign up to set email alerts
|

LRG1 promotes angiogenesis through upregulating the TGF-β1 pathway in ischemic rat brain

Abstract: Stroke is a life-threatening disease that results in significant disability in the human population. Despite the advances in current stroke therapies, a host of patients do not benefit from the conventional treatments. Thus, more effective therapies are required. It has been previously reported that leucine-rich-α2-glycoprotein 1 (LRG1) is crucial during the formation of new blood vessels in retinal diseases. However, the function of LRG1 in the brain during the neovessel growth process following ischemic stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 42 publications
2
41
1
Order By: Relevance
“…LRG1 has been identified to be positive in endothelial cells owing to its mitogenic activities, thus resulting in the improvement of angiogenesis 10 . Moreover, a previous study demonstrated that, in rats with middle cerebral artery occlusion, LRG1 could promote angiogenesis via the upregulation of the transforming growth factor-β (TGF-β) signaling pathway 11 . Another study also concluded that the migratory machinery of cells was associated with LRG1, because their activities were altered as observed in their performance within the non-canonical TGF-β signaling pathway 12 .…”
Section: Introductionmentioning
confidence: 99%
“…LRG1 has been identified to be positive in endothelial cells owing to its mitogenic activities, thus resulting in the improvement of angiogenesis 10 . Moreover, a previous study demonstrated that, in rats with middle cerebral artery occlusion, LRG1 could promote angiogenesis via the upregulation of the transforming growth factor-β (TGF-β) signaling pathway 11 . Another study also concluded that the migratory machinery of cells was associated with LRG1, because their activities were altered as observed in their performance within the non-canonical TGF-β signaling pathway 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Of note, increased levels of TGF‐β were reported in the plasma of stroke patients (Yan, Greer, & McCombe, ) and its expression was induced in the murine brain following ischemia (Zhang et al, ). TGF‐β has been implicated in processes of post‐stroke recovery, including glial scaring and angiogenesis (Meng et al, ; Pardali, Goumans, & ten Dijke, ; Zhu et al, ). In line with these findings, we detected increased levels of TGF‐β1 in the ipsilateral hemispheres of the WT brains 3 days after MCAo (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…lncRNA NONMMUT058334 expression correlated negatively with that of Orly, Dux, Speer4d , and Tango6 , and lncRNA NONMMUT000708 expression correlated positively with that of Hif3a . The mRNAs in the co-expression network were involved in inflammation, neuronal apoptosis, and metabolic pathways [ 33 35 ]. Our findings suggest that these differentially expressed lncRNAs participate in POCD by interacting with their corresponding coding genes.…”
Section: Discussionmentioning
confidence: 99%